Points of View and Readers’ Immersion in Translation: A Neurocognitive Interpretation of Poetic Translatability - Chen, Qing; Shen, Lin; Ochs, Shelley; Xiao, Kairong (Frontiers in Psychology, 2022)
There have been few attempts at applying cultural neuroscience and psychology to the discussion of poetic translatability. This study employs cultural neuroscience and psychology methodologies and forms of evidence to explore the neurocognitive mechanisms by which cross-cultural variations in perspectives during the translation process influence poetic reception in the target culture. The English translation of Chinese poetry is often tasked with the supplement of perspectives and accompanied by cross-cultural variations of immersion. These changes have been substantially discussed from literary and poetic perspectives but remain understudied in terms of their neurocognitive and psychological implications. Through textual analysis of first-person points of view, this study attempts to apply neuroscience to the interpretation of the impact of differences in cross-cultural perspectives in poetry translation. Our findings suggest that a general tendency toward the supplement of first-person perspectives could boost the immersive experience by activating mirror neurons and the temporal parietal junction. These neuroscientific mechanisms underlying the observable cultural phenomenon offer implications for the translation of Chinese poetry in a way that generates brain responses and neurotransmitters similar to the source text. This study demonstrates how research in neuroscience can illuminate findings in cross-cultural communication.